Anaerobic methane oxidation in a coastal oxygen minimum zone: spatial and temporal dynamics. (25th April 2022) - Steinsdóttir, Herdís G. R.; Gómez‐Ramírez, Eddy; Mhatre, Snehit; Schauberger, Clemens; Bertagnolli, Anthony D.; Pratte, Zoe A.; Stewart, Frank J.; Thamdrup, Bo; Bristow, Laura A.
Summary: Coastal waters are a major source of marine methane to the atmosphere. Particularly high concentrations of this potent greenhouse gas are found in anoxic waters, but it remains unclear if and to what extent anaerobic methanotrophs mitigate the methane flux. Here we investigate the long‐term dynamics in methanotrophic activity and the methanotroph community in the coastal oxygen minimum zone (OMZ) of Golfo Dulce, Costa Rica, combining biogeochemical analyses, experimental incubations and 16S rRNA gene sequencing over 3 consecutive years. Our results demonstrate a stable redox zonation across the years with high concentrations of methane (up to 1.7 μmol L −1 ) in anoxic bottom waters. However, we also measured high activities of anaerobic methane oxidation in the OMZ core (rate constant, k, averaging 30 yr −1 in 2018 and 8 yr −1 in 2019–2020). The OPU3 and Deep Sea‐1 clades of the Methylococcales were implicated as conveyors of the activity, peaking in relative abundance 5–25 m below the oxic–anoxic interface and in the deep anoxic water respectively. Although their genetic capacity for anaerobic methane oxidation remains unexplored, their sustained high relative abundance indicates an adaptation of these clades to the anoxic, methane‐rich OMZ environment, allowing them to play major roles in mitigating methane fluxes.